The Counter case of the United States before the Tribunal of Arbitration to convene at Paris under the treaty between the United States of America and Great Britain, concluded February 29, 1892 [electronic resource] : including appendix. - Ross siĭsko-amerikanskai͡a kompan sii͡a.; Bering Sea Tribunal of Arbitration.; United States. (Washington : G.P.O., 1893)
With 39 leaves of facsimiles of manuscript documents from the Ross si ̆isko-amerikanskai͡a kompan sii͡a (i.e. Russian-American Company). At head of title: Fur-seal arbitration. Includes indexes. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44